You Pay a Fee for Strong Beliefs: Homogeneity as a Driver of Corporate Governance Failure - Katja Rost; Margit Osterloh (Center for Research in Economics, Management and the Arts (CREMA), 2008)
The financial crisis made apparent the fact that managers and the boards of banks had failed to see the implications of irrational behavior and had ignored the risk associated with group think. Taking data from Switzerland our study shows that there is an increasing homogeneity of management and board teams. Most committees mainly consist of males with a managerial background. We derive from the existing literature the hypotheses that in radically changing environments women and individuals without a managerial background are less affected by systematic forecasting errors. Using a dataset collected shortly before the peak of the financial crisis we demonstrate that the groups which are highly underrepresented in most boards and management teams were significantly more capable of giving correct forecasts than the groups generally best represented in boards and management teams. To mitigate corporate governance failures we argue that firms should use simple social mechanisms in order to increase the diversity of their management and board teams while at the same time avoiding the danger of time consuming team conflicts. They should therefore include criss-cross individuals, i.e. individuals with no clear-cut group affiliation such as males with a nonmanagerial background as well as women with a management-related background.
Keywords: 330; Board diversity; psychological economics; forecasting predictions; gender; expert knowledge; uncertainty